Kajian potensi tanaman aromatik untuk penggunaannya dalam lanskap terapeutik (studi kasus: BSIP TROA) - Sayyidah Khairunnisa; Nizar Nasrullah; Prita Indah Pratiwi (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Therapeutic landscape is a green public space that benefits the physical, mental, and social health of the community. Aromatic plants are one of the essential elements in the therapeutic landscape that can provide calming effects, reduce stress, and so on. This study aims to identify types of aromatic plants, assess the therapeutic function and aroma level, compile aromatic plant recommendations, and create a model of aromatic plant arrangement. The research was conducted at BSIP TROA, which has various collections of aromatic plants. The data needed for assessing plant therapy function were taken by survey technique and analyzed using the scoring method based on therapeutic function criteria. Aroma level assessment data was taken from the aroma perception evaluation questionnaire to 30 BSIP TROA visitors and processed by cluster analysis. The results showed there are 40 potential aromatic plant species, including 19 trees, 16 shrubs, two climbers, two ground covers, and one aquatic plant. Combining all the therapeutic function scores, aromatic plants with excellent scores totaling six species, good scores totaling 31 species, medium scores totaling three species, and no species with bad scores.